Maximum Fractal Dimension of Cerebral Seizure Remains Constant Through the Course of Electroconvulsive Therapy. (April 2014) - Rakesh, Gopalkumar; Abhishekh, Hulegar A.; Thirthalli, Jagadisha; Phutane, Vivek H.; Muralidharan, Kesavan; Candade, Vittal S.; Gangadhar, Bangalore N.
Electroconvulsive therapy (ECT), in which electrical current is used to induce seizures, is an effective treatment in psychiatry. Different methods of analyzing the electroencephalogram (EEG) changes during ECT have been studied for predicting clinical outcome. Analysis of the fractal dimension (FD) is one such method. Mid-seizure and post-seizure FD has been shown to correlate with antidepressant effect. In this study, we examined whether the highest fractal dimension achieved during each ECT session changed over the course of 6 ECTs. The sample for this study came from a randomized controlled trial, comparing the efficacy of bifrontal and bitemporal electrode placements in schizophrenia. EEG was recorded using bilateral frontal pole leads during all ECT sessions. In 40 of the 114 randomized patients, we could obtain artifact-free EEGs for the first 6 ECT sessions. FD was calculated using standardized algorithms. For each session, the average of 5 highest FDs was calculated. The change in this value over a course of 6 ECTs was analyzed using repeated-measures analysis of variance. The average highest FD remained virtually unchanged across the 6 ECT sessions. Means (standard deviations) average maximum FDs over the 6 sessions were 1.57 (0.075), 1.57 (0.064), 1.56 (0.064), 1.57 (0.062), 1.55 (0.07), and 1.56 (0.067); occasion effect, F = 0.5, P = .75. Group effect ( F = 0.01, P = .92) and group × occasion interaction effect ( F = 1.88, P = .1) were not significant, suggesting no influence of electrode placement on maximum FD. Seizure duration, however, showed significant decline over the course of ECT. Maximum FD of ECT-induced EEG seizure remains fairly constant over frontal poles across the first 6 ECT sessions, which is true irrespective of ECT electrode placements.